Development and validation of a semi-quantitative food frequency questionnaire to assess dietary intake in Turkish adults - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2015)
Objectives: To validate the original food frequency questionnaire in Turkish adult population. Methods: The cross-sectional study was conducted in June and December 2008 and 2009, and comprised adults of either gender aged 30-70 years. All subjects were Caucasians and were native Turkish speakers. The food frequency questionnaire containing 229 most frequently consumed foods under 7 topics was used for data collection. It was completed twice and the 24-hour dietary recall four times in a year. In order to assess the validity of the questionnaire, Pearson correlation, attenuation coefficient, measures of agreement between the two methods, weighted kappa statistics and Bland-Altman plots were employed. SPSS 16 was used for statistical analysis. Results: Of the 120 subjects in the study, 71(59%) were males and 49(41%) were females with an overall mean age of 50.16 +/- 9.76 years. The correlation of estimated nutrient intake between the food frequency questionnaire and 24-hour dietary recall varied between 0.200 and 0.468, energy-adjusted regression was between 0.044 and 0.611 and attenuation coefficients of regression were between 0.339 and 0.658 for the selected macro and micro nutrients. Bland-Altman plots showed an acceptable agreement between the two methods. When nutrient intake was categorised in quartiles, proportions of the same or adjacent quartiles were 98.3%, 98.4%, 98.3%, 96.7% and 95% for energy, fat, protein, carbohydrates and fibre, respectively. Conclusion: The first food frequency questionnaire developed in Turkish language was an adequate and valid tool to assess the nutritional habits of the local population.
Keywords: Food frequency questionnaire (FFQ); 24-hour dietary recall (24HR); Dietary assessment; Validation; RELATIVE VALIDITY; PROSPECTIVE URBAN; HIGH-INCOME; REPRODUCIBILITY; QUALITY; POPULATION; CANCER; DESIGN; MIDDLE; PURE